Pengaruh Sales Promotion Kosmetik Secondate Di Instagram Terhadap Keputusan Pembelian Konsumen: Survei Pada Followers Instagram @secondatebeauty - Zahra Khoerrunissa; Oktaviana Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2024)
With advances in information and communication technology, with the presence of the internet, the internet is often used as a means of communication, namely what we usually call social media. The business world is currently contributing to online promotions via social media, one of which is cosmetic products, namely Secondate. This research aims to determine sales promotion in a Secondary purchasing decision and determine the influence of sales promotion on purchasing decisions. The theory used in this research is marketing communication from Hermawan 2012 and Kotler & Keller's sales promotion theory which includes discounts, game contests and sweepstakes, package prices, premiums, and related promotions. The theory used in purchasing decisions from Kotler & Keller includes problem recognition, information search, alternative evaluation, purchasing decisions, and post-purchase behavior. The approach used in this research is a quantitative approach with survey methods and data collection techniques carried out using questionnaires. The population in this study was 354 and the sample used was 78 respondents using the Slovin formula.